STRUKTUR DAN KOMPOSISI JENIS VEGETASI RIPARIAN KEBUN RAYA SAMBAS KABUPATEN SAMBAS KALIMANTAN BARAT - Lestari, Andriyani; Dewantara, Iswan; Ardian, Hafiz (Universitas Tanjungpura, 2018)
Riparian vegetation is a natural resource that is easily distrubed due to stabilization by human’s hand in ordinary rivers or within the scope of conservation areas such as botanical gardens. Riparian vegetation plays an important role in maintaining the ecosystem stability of river, where the endemic wild animals are and maintaining the quality of sorrounding water. The purpose of this research is to analyze the stucture and compositio of dominant kinds and species of tree vegetation in riparian based Sambas Botanical Garden, Sabung village, Sabuh Sambas district, West Kalimantan. The method used in this study is survey with the combination of plant lanes technique , the spaces between two rows pf plants, and a line method. Observation tracks are made and placed in front of the vegetation. The placement of the observation line is purposely set to present the middle, upstream and downstream river areas on the river bank of ±105 Ha. To analyze the area, the observation line was made about 6 lanes, with the lenght of each path was adjusted to the tide level approaching the land based on the existing hydrological cycle map to obtain 6 lanes with different lenghts. For each of these lines a 20m x 20 m observation plot was made for tree level observation, 10m x 10m for pole observation, 5m x 5m for observation of piles, and 2m x 2m for observation of plant seeding rates. The process of seeding vegetation structure in riparian botanical garden was found complete from seedling, sapling, and poles to trees. The composition of riparian forest vegetation species consist of 22 species of vegetation, 14 families, and 18 genera with diversity for each low growth rate of less than 1, with pattern of spreading concentration and not concerntrated in one particular species. Therefor, with the discovery of the Hibiscus tilliaceus species at all growth rates, this species can be regarded as an indicator of ecosystems as a riparian forest ecosystem in Sambas Botanical Garden.Keyword : Diversity, Ecological Function, Hibiscus tilliaceus, Riparian